ICSSP 2018—Special issue introduction. Issue 5 (20th May 2019) - O'Connor, Rory V.; Houston, Dan; Hebig, Regina; Kuhrmann, Marco
Abstract: The International Conference on Software and System Processes (ICSSP) provides a leading forum for the exchange of research outcomes and industrial best practices in process development from software and systems disciplines. ICSSP 2018 was held in Gothenburg, Sweden, May 26 to 27, 2018, colocated with the 40th International Conference on Software Engineering (ICSE). The theme of ICSSP 2018 was studying "Demands on Processes, Processes on Demand" by recognizing the demands on processes that include the need for both well‐developed plans and incremental deliveries (agile and hybrid processes), utilization of increased automation (model‐based engineering and DevOps), higher degrees of customer collaboration, comprehensive analysis of existing products for reuse (open source and COTS), and performance requirements of enterprise‐level architectures. This special issue includes the revised and extended versions of the five highest ranked full research papers and industry experience papers of ICSSP 2018, including the two award‐winning papers.